(untitled) (Bangladesh Journal of Medical Science, 2015)
Arthrogryposis multiplex congenita (AMC) refers to a group of conditions, unrelated to one another, which are similarly characterized by the contracture of multiple joints in the body. One of the common therapies in patients with AMC and knee extension contracture is quadricepsplasty. However, no comprehensive studies have been conducted on the results of the application of this method. This prospective study included 14 patients (9 females and 5 males) with 23 hyperextension contractures of the knee. Before surgery, all patients had underwent non-surgical treatment (manipulation and serial casting) for at least 6 months, but none had responded to the treatment. Then patients underwent a Quadricepsplasty. Range of motion (ROM) of the knee and patients ambulation based on modified form of Functional Mobility Scale (FMS) before and after surgery were evaluated in a follow up 3 years. The mean passive knee ROM before surgery was 7.17° (0° to 15°), which increased to 65.65° (35° to 105°) after the operation. According to t-test results, this increase was statistically significant (P<0.005). The mean ambulation score (modified FMS) of the patients before surgery was 1.57, which increased to 3.71. According to t-test results, this increase was statistically significant (P<0.005). Quadricepsplasty is the method of choice for the surgical treatment of knee extension contracture in AMC patients, who do not respond to non-surgical treatments. This method leads to a significant improvement in knee ROM. On the other hand, it preserves quadriceps strength at 4/5 level, and finally, along with other therapeutic interventions for other lower limb deformities, leads to ambulation improvement in these patients. Bangladesh Journal of Medical Science Vol.14(4) 2015 p. 331-335